2015
DOI: 10.1097/ta.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric trauma center and the inclusive trauma system

Abstract: Therapeutic study, level IV; epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…As shown in Table 2, tertiary centers had a higher percentage of patients with an ISS ≥ 16 than noncenter hospitals during every period of the study. These results are similar to the results of previous studies [11, 12]. The well-established infrastructure, facilities for immediate resuscitation and angiography, 24-h availability of the ICU and confidence of the trauma team might be influencing factors of this result [13].…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Table 2, tertiary centers had a higher percentage of patients with an ISS ≥ 16 than noncenter hospitals during every period of the study. These results are similar to the results of previous studies [11, 12]. The well-established infrastructure, facilities for immediate resuscitation and angiography, 24-h availability of the ICU and confidence of the trauma team might be influencing factors of this result [13].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, CT scan should not be the only factor guiding the diagnostic process; and some authors use this argument to avoid imaging in a stable patient altogether. Surprisingly, several studies have shown that adherence to APSA guidelines is low in non-pediatric trauma centers [ 145 , 162 , 168 172 ]. Pediatric trauma patients treated in dedicated centers were demonstrated to have higher probability to undergo NOM than those treated in adult trauma centers [ 145 , 162 , 168 170 ].…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…Surprisingly, several studies have shown that adherence to APSA guidelines is low in non-pediatric trauma centers [ 145 , 162 , 168 172 ]. Pediatric trauma patients treated in dedicated centers were demonstrated to have higher probability to undergo NOM than those treated in adult trauma centers [ 145 , 162 , 168 170 ]. Mooney et al and Todd et al demonstrated that children with splenic injury have a greater chance to undergo splenectomy or laparotomy in general if treated in an adult trauma center [ 171 , 173 ].…”
Section: Pediatric Patientsmentioning
confidence: 99%
“…Injury is a leading cause of death among the young everywhere in the world and the top global killer of adolescents (100). Findings from high-income countries suggest that dedicated systems of care for injured children can avert deaths and disability (72,76). In LMICs, pediatric-specific trauma care resources and expertise are more often deficient than those for general trauma care (2,11,75); planning and organizing care for injured children should be a priority area for research and system development, given the large burden of pediatric injury in LMICs.…”
Section: Wwwannualreviewsorg • the Impact Of Trauma Care Systems Inmentioning
confidence: 99%